RESPONSE OF PHULE JYOTI (CAPSICUM ANNUUM L.) CUITIVAR TO FOLIAR APPLICATION OF BLUE GREEN ALGAL EXTRACT, BIOFORCE, AMRUTA AND RECOMMENDED DOSE. - A.R.ABHANG (International Journal of Pharma and Bio Sciences, 2013)
Investigation to study the effect of Blue-green algal extract, Bioforce, Amruta (19:19:19) and recommended dose (NPK) as foliar sprays on growth of chilli Phule-Jyoti was carried out on farmers field at Yeole Akhada village of Ahmednagar district. The experiment was laid out in randomized block design with three replication. This experiment consists of eight foliar spray treatments. Among the treatments, foliar application of blue-green algal extract was significantly superior to other treatments in increasing the yield of chilli fruits. The highest yield of chilli 171 q/ha. was recorded with the application of blue-green algal extract.